Employee Retention Enhancement Strategy to Reduce Turnover Rate at CV XYZ - Tsurayya Az-Zahra; Ratri Wahyuningtyas (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The high employee turnover rate at the CV XYZ camping ground indicates a human resource management problem that affects organizational stability, service quality, and operational effectiveness. This research aims to identify the factors contributing to employee turnover and formulate relevant employee retention strategies. The research employs a qualitative approach using a case study method through in-depth interviews, observations, documentation, and literature reviews. The results reveal six main factors contributing to employee turnover: resistance to organizational change; leadership, communication, and supervision; integrity, discipline, and governance; work environment and organizational climate; psychological and cultural safety; and compensation and compensation fairness. The SWOT analysis indicates that the organization is positioned in the Grow and Build quadrant. This research develops nine employee retention strategies categorized into three levels of implementation: Corrective Strategies, Retention Strengthening Strategies, and Competitive Advantage Strategies. The study concludes that effective employee retention strategies should be implemented systematically through improvements in turnover-related factors, strengthening of the human resource management system, and optimization of competitive advantages. The findings are expected to provide practical guidance for CV XYZ in reducing sustainable employee turnover and serve as a reference for future research.